Mesenchymal Stem Cell-Based Therapy for Stroke: Current Understanding and Challenges - Li, Weifeng; Shi, Linli; Hu, Bei; Hong, Yimei; Zhang, Hao; Li, Xin; Zhang, Yuelin (Frontiers in Cellular Neuroscience, 2021)
Stroke, the most prevalent cerebrovascular disease, causes serious loss of neurological function and is the leading cause of morbidity and mortality worldwide. Despite advances in pharmacological and surgical therapy, treatment for functional rehabilitation following stroke is limited with a consequent serious impact on quality of life. Over the past decades, mesenchymal stem cell (MSCs)-based therapy has emerged as a novel strategy for various diseases including stroke due to their unique properties that include easy isolation, multipotent differentiation potential and strong paracrine capacity. Although MSCs have shown promising results in the treatment of stroke, there remain many challenges to overcome prior to their therapeutic application. In this review, we focus on the following issues: the scientific data from preclinical studies and clinical trials of MSCs in the treatment of stroke; the potential mechanisms underlying MSC-based therapy for stroke; the challenges related to the timing and delivery of MSCs and MSC senescence.